2013
DOI: 10.3947/ic.2013.45.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Basis for Methicillin Resistance inStaphylococcus aureus

Abstract: Since the discovery of the first strain in 1961 in England, MRSA, the most notorious multidrug-resistant hospital pathogen, has spread all over the world. MRSA repeatedly turned down the challenges by number of chemotherapeutics, the fruits of modern organic chemistry. Now, we are in short of effective therapeutic agents against MRSA prevailing among immuno-compromised patients in the hospital. On top of this, we recently became aware of the rise of diverse clones of MRSA, some of which have increased pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
151
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(166 citation statements)
references
References 111 publications
9
151
1
5
Order By: Relevance
“…In these strains, these elements are mainly associated with SCCmec (Chambers & Deleo, 2009;Hiramatsu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In these strains, these elements are mainly associated with SCCmec (Chambers & Deleo, 2009;Hiramatsu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…SCC elements are large segments of DNA that carry variable arrays of genes, which can include genes that encode resistance to antibiotics other than meticillin. Diverse SCCmec types (SCCmec types I-XI) have been described [3]. Acquisition of other mobile genetic elements (MGEs) carrying virulence genes and other antibiotic resistance determinants may lead to further adaptation of MRSA lineages [4].…”
Section: The Emergence Of Mrsamentioning
confidence: 99%
“…Within resistance mechanism to b-lactam antibiotics, the mecA gene plays the keystone role, and confirming its presence has been established as a 'diagnostic dogma' to categorize an isolate as methicillin-resistant staphylococci (MRS). However, more recent studies have demonstrated that this approach does not take into account that phenotypic methicillin (and other blactam) resistance in Staphylococcaceae is conferred not only by mecA but also by the homologous genes mecB and mecC (Hiramatsu et al, 2013;Becker et al, 2014b). Even if the origin of mecA gene in methicillin-resistant Staphylococcus aureus (MRSA) remains unknown, several studies have demonstrated its high similarity degrees with mecA of Staphylococcus sciuri and Staphylococcus fleurettii, suggesting that these might be sources of mecA precursor (Wu et al, 1996;Tsubakishita et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are similar MGEs harbouring capsule group 1 factors of S. aureus, the fusidic acid resistance gene fusB/Q6GD50, several heavy metal resistance operons, enterotoxin H and the arginine catabolic mobile element, all of which can be found in different Staphylococcaceae members. This MGE is considered to confer better survival ability and increased virulence to the strain (Monecke et al, 2012;Hiramatsu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%